Estimation of Monthly Average Daily Diffuse Solar Radiation using Empirical Models For Kathmandu Nepal - Pandey, B.; Aryal, R. P.; Gnawali, C. L.; Poudyal, K. N.; Karki, I. B.; Koirala, I. (Journal of Nepal Physical Society, 2019)
An accurate knowledge and data of solar radiation and its component are indispensable for the utilization of solar energy. However radiation data are often inaccessible. In this regard, the empirical models are reliable tools. This paper aims to develop and evaluate three simple empirical models (linear, quadratic, and cubic) for estimation of monthly average daily diffuse solar radiation of Kathmandu. Developed Models correlates diffuse fraction with clearness index are based on the satellite data from the NASA Langley Research Center. The performance of models is found to be statistically significant which has been analyzed in terms of statistical indicators like RMSE, MBE and R2. Among the three models, the cubic model is best fit on the basis of statistical parameters. So that cubic model is recommended for the estimation of monthly average daily diffuse radiation at Kathmandu and similar climatic sites of Nepal.